The influence of 4Ps, marketing mix towards customer satisfaction: a case study of Pasar Bergerak 1 Malaysia in rural area / Nur Syafiqah Musa - Musa, Nur Syafiqah (2016)
Pasar Bergerak 1Malaysia is a new marketing channel that has been introduced by Federal Agriculture Marketing Association (FAMA). One of the rising issues from Pasar Bergerak 1Malaysia is their sales is not achieved FAMA goals. Recent observation has been done to know in depth about the issue related with PBIM. The researcher has asked one asked one of their officers related to the PBIM issues. So, the problems come from themselves such as the product they served, price they offered , the location also the promotion they do in order to attract their target market. Besides, they have crucial issues which is there is gap between rural area sales and urban area sales. Consequently, sales problem always generate from the customer satisfaction issue. Therefore, this study aims to investigate the influences of marketing mix towards customer satisfaction. This study focuses on marketing mix model which is 4Ps concept. This marketing mix is involving the four elements which are product, place, place and promotion. The result of this study will be obtained from distribution of 90 questionnaires to Parit Raja citizens in order to identify their views about PBIM marketing mix and will it leads to customer satisfaction. The study use qualitative method approach as the primary data. While for secondary data, the researcher uses the journal and internet as the guidance .